2021
DOI: 10.24036/jea.v3i1.354
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Keterlambatan Laporan Pertanggungjawaban Realisasi APBDes (Nagari)

Abstract: This study aims to describe why the village goverment is late in submitting the village budget accountability report (APBDes) in West Pasaman Regency. This research is classified as a descriptive study. Sampling based on research objectives and data collection methods using interviews. This research was conducted in villages that were late in reporting the accountability for the realization of the (APBDes) in West Pasaman Regency. This study found that there are four obstacles that cause the village apparatus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Previous research in Limpung Subdistrict, Batang Regency, showed that organizational culture directly affects the performance of village officials (S et al, 2022). Previous research in West Pasaman Regency, West Sumatra, conducted direct observations, and the results showed that internal control affected the timeliness of reporting the Village Budget (Rafsanjani & Cheisviyanny, 2021). Previous research in Sumorame Village, Candi District, and Sidoarjo Regency showed that the community still did not realize the importance of transparency for public welfare, and transparency by the Village Government only served to achieve specific formality goals based on implementing applicable regulations (Ardelia & Handayani, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research in Limpung Subdistrict, Batang Regency, showed that organizational culture directly affects the performance of village officials (S et al, 2022). Previous research in West Pasaman Regency, West Sumatra, conducted direct observations, and the results showed that internal control affected the timeliness of reporting the Village Budget (Rafsanjani & Cheisviyanny, 2021). Previous research in Sumorame Village, Candi District, and Sidoarjo Regency showed that the community still did not realize the importance of transparency for public welfare, and transparency by the Village Government only served to achieve specific formality goals based on implementing applicable regulations (Ardelia & Handayani, 2022).…”
Section: Introductionmentioning
confidence: 99%